(untitled) (Journal of Accessibility and Design for All, 2025)
This paper analyses the social, cultural and urban factors influencing the mobility of older adults in Guadalajara, Mexico. Specifically, it addresses the experiences of 18 elderly within their immediate urban environment, identifying the environmental pressures they encounter during their movements. The study maps destinations that satisfy needs shaped by participant’s culture and identifies the emotional resources and social capital that support older adults in accessing these destinations. The findings reveal that mobility barriers arise not only from non-universal design but also from a fragile social-institutional framework, primarily reflected in an environment perceived as unsafe.